News Writing for Print - Ricky Telg; Lisa Lundy (EDIS)
This publication about news writing for print is the second of a five-part series on news media writing. This series also covers an introduction to news media writing, grammar and punctuation, news writing for television and radio, and interviews for news stories. Minor revision by Ricky Telg and Lisa Lundy. Published by the UF/IFAS Department of Agricultural Education and Communication. 5pp.